Mouse hippocampal GABAB1 but not GABAB2 subunit-containing receptor complex levels are paralleling retrieval in the multiple-T-maze - Falsafi, Soheil K.; Ghafari, Maryam; Miklósi, András G.; Engidawork, Ephrem; Gröger, Marion; Höger, Harald; Lubec, Gert (Frontiers in Behavioral Neuroscience, 2015)
GABAB receptors are heterodimeric G-protein coupled receptors known to be involved in learning and memory. Although a role for GABAB receptors in cognitive processes is evident, there is no information on hippocampal GABAB receptor complexes in a multiple T maze (MTM) task, a robust paradigm for evaluation of spatial learning. Trained or untrained (yoked control) C57BL/6J male mice (n=10/group) were subjected to the MTM task and sacrificed 6 hours following their performance. Hippocampi were taken, membrane proteins extracted and run on blue native PAGE followed by immunoblotting with specific antibodies against GABAB1, GABAB1a and GABAB2. Immunoprecipitation with subsequent mass spectrometric identification of co-precipitates was carried out to show if GABAB1 and GABAB2 as well as other interacting proteins co-precipitate. An antibody shift assay (ASA) and a proximity ligation assay (PLA) were also used to see if the two GABAB subunits are present in the receptor complex. Single bands were observed on Western blots, each representing GABAB1, GABAB1a or GABAB2 at an apparent molecular weight of approximately 100 kDa. Subsequently, densitometric analysis revealed that levels of GABAB1 and GABAB1a but not GABAB2- containing receptor complexes were significantly higher in trained than untrained groups. Immunoprecipitation followed by mass spectrometric studies confirmed the presence of GABAB1, GABAB2, calcium calmodulin kinases I and II, GluA1 and GluA2 as constituents of the complex. ASA and PLA also showed the presence of the two subunits of GABAB receptor within the complex. It is shown that increased levels of GABAB1 subunit-containing complexes are paralleling performance in a land maze.